Expériences carcérales et traductions picturalesLe témoignage du peintre et objecteur de conscience Didier Poiraud durant et après la guerre d’indépendance algérienne (1961-1964) - Marc André (L’Année du Maghreb)
The Algerian War has long been considered a “war without images”, owing to a combination of state censorship and the self-censorship of artists themselves. However, recent research has revealed numerous art works preserved thus far in the privacy of personal archives. This article follows the trajectory of a conscientious objector, member of the Non-violent Civic Action group, whose detention drawings depict his everyday life as an inmate in several prisons and camps. Pursued and arrested for illegal protest, disobedience, and desertion, this artist-objector was detained and incarcerated eleven times at various detention sites in France. Didier Poiraud’s experiences shed light on the conditions under which wartime artwork can emerge and on the detention conditions faced by conscientious objectors. By carefully observing his drawings - shown here for the first time - and by analyzing them in the context of their production, we gain a better understanding of the relentless and arbitrary repression to which conscientious objectors were subjected during the Algerian War. Through his artwork, resistance in prison can be reinscribed within a larger fight that not only contested the decolonisation war but also led to the reformation of the military service.